Education Capitalization and Learning Accesstability - Idham Okalaksana Putra; Abdul Muhid (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2021)
Education has a much needed role for everyone to give new knowledge. Education requires materials that support it to be well-maintained. In accordance with the opening of the Contstitution 1945 is educate the life of the nation. Lately, education is used as a new tool to gain profit from all aspects in other words of the commercialization of education. The capitalization of this education can be felt by the parties who have a level of opinion below the average, they struggle to get the best education. Because good education requires complete and good facilities. The implementation can be seen from the expensive costs incurred to obtain the facility. Good education requires complete and good facilities. The implementation can be seen from the expensive costs incurred to obtain the facility. Every citizen has access to a decent education to foster their learning interest.